E-026 Superselective pharmacologic functional testing of a lenticulostriate vessel originating from an intracranial aneurysm before endovascular treatment. (16th November 2010) - Toth, G; Haithcock, J; White, J; Pride, L
Abstract : Introduction: Incorporation of branch vessels into intracranial aneurysms represents a potential limitation to endovascular treatment, since these arteries may supply eloquent brain territory. While neck remodeling with balloons and stents have allowed treatment of complex anatomic configurations, incorporated small perforators may not be as reliably protected with these techniques. In such cases, surgical clipping may be a better alternative to maintain branch vessel patency while allowing obliteration of the fundus. Clinical consequences of perforator vessel occlusion during endovascular or open surgery are often unpredictable. Possible outcomes range from no symptoms to devastating neurologic deficits. Pharmacologic functional testing has been widely utilized to assess operative risks for brain/spinal cord vascular malformations and epilepsy but limited data are available on superselective testing for aneurysm treatment. Objective: We report a case where intra-aneurysmal functional testing allowed successful endovascular treatment of a previously clipped, recurrent proximal middle cerebral aneurysm that incorporated a large lateral lenticulostriate artery into the fundus. Our goal is to discuss endovascular technique and possible clinical symptoms resulting from perforator occlusion. We also review cerebrovascular functional testing for intracranial aneurysms. Methods: A standard microcatheter was used to access the right middle cerebral artery (MCA) aneurysm under minimal conscious sedation. Functional testing was completed by slowly injecting sodium amobarbital into the aneurysm fundus and incorporated lenticulostriate vessel. Serial neurologic examinations identified no new deficits and we proceeded with endovascular coiling. For comparison and review, we searched the current literature via standard online resources for functional testing of intracranial aneurysms and perforating artery occlusive syndromes. Results: Successful coiling of the MCA aneurysm was performed after unremarkable intra-aneurysmal testing. Complete obliteration of the aneurysm was achieved. A small infarct was seen on follow-up CT at the right caudate head but the patient developed no associated neurologic deficit. He was discharged home the next day and remains asymptomatic. If symptomatic, lenticulostriate occlusions may result in hemiparesis, sensory deficit, speech changes, confusion, neglect and seizure. There are published cases of supraselective testing before parent vessel occlusion for distal intracranial aneurysms but no reports describe targeted intra-aneurysmal testing of an incorporated perforator. Conclusion: We report a unique case of successful superselective pharmacologic testing of a lenticulostriate vessel originating directly from an intracranial aneurysm. Microcatheter directed intra-aneurysmal functional testing reliably predicted an asymptomatic small basal ganglia infarct, allowing safe endovascular treatment in our patient. This procedure should be considered for complex intracranial aneurysms with uncertain treatment outcome due to perforator vessels arising from the fundus.